TYPOLOGY OF CREDIT RISK IN ECONOMY - Marinela BARBULESCU; Alina HAGIU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2019)
Today, many techniques are known regarding credit risk management, starting from traditional techniques of risk exposure assessment, aimed at limiting excessive concentration at the level of the debtor, sector of activity, industrial branch, etc., until the new management techniques, modern, such as swap transactions and options, adapted to this type of risk. Thus, the instability led to an unprecedented development of counterparty risk, in general and credit risk in particular, determined the concerns regarding the management of this type of risk by expanding and even applying more and more generalized performant techniques of credit risk assessment.